Determination of aluminum concentrations in biological specimens: application in the clinical laboratory - San Martín Sonia Pérez; Bauçà Josep Miquel; Martinez-Morillo Eduardo (Advances in Laboratory Medicine, 2022)
Aluminum enters the body primarily through diet or occupational exposure, and is cleared through urine. However, this trace element may accumulate and cause toxicity in subjects with renal insufficiency, and even in dialysis patients. The mechanism of aluminum toxicity is related to increased oxidative and inflammatory stress, iron and calcium dyshomeostasis, or cholinergic dysregulation, among other. A review was conducted on the specimens and analytical methods used to determine aluminum in biological specimens and dialysis water. This paper describes the most relevant aspects related to quality assurance. This is a practical guideline for the development and implementation of a reliable method for determination of aluminum in the clinical laboratory. Serum aluminum is the main biomarker of toxicity. For cases of chronic exposure, urine testing is recommended. At present, inductively coupled plasma mass spectrometry (ICP-MS) is the gold-standard determination method, since it has been proven to have the best quantification limits, selectivity and robustness. Clear recommendations are provided in relation to the specimens used for aluminum determination. Relevant pre-analytical, analytical, and post-analytical considerations are also presented.